2024
DOI: 10.1037/ser0000762
|View full text |Cite
|
Sign up to set email alerts
|

Examining the outcomes and acceptability of a peer-led spiritual intervention for moral injury in a veteran service organization.

Abstract: The purpose of this proof-of-concept study was to examine the outcomes and acceptability of a spiritual intervention for moral injury led by veteran peers in a Veteran Service Organization (VSO), called "Heroes to Heroes." From baseline to 1-year follow-up, 101 veterans who participated in the intervention completed the evaluation surveys at four time points assessing psychological outcomes (moral injury, posttraumatic stress disorder [PTSD] symptoms, and life satisfaction), spiritual outcomes (spiritual strug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Several previous studies have reported on MI interventions developed and delivered by chaplains (see the scoping review from Jones et al, 2022 and Currier et al, 2023 ) but we believe that this is the first to use a qualitative methodology to explore the support provided by chaplains in routine practice and how this support is received by police members. The initial scope of enquiry was the nature of support sought and provided following the experience of a PMIE but as noted in the results, the types of moral transgressions described by both police members and police chaplains varied on a continuum of severity, which included, but was not limited to, PMIEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have reported on MI interventions developed and delivered by chaplains (see the scoping review from Jones et al, 2022 and Currier et al, 2023 ) but we believe that this is the first to use a qualitative methodology to explore the support provided by chaplains in routine practice and how this support is received by police members. The initial scope of enquiry was the nature of support sought and provided following the experience of a PMIE but as noted in the results, the types of moral transgressions described by both police members and police chaplains varied on a continuum of severity, which included, but was not limited to, PMIEs.…”
Section: Discussionmentioning
confidence: 99%
“…While the support currently provided by chaplains aligns closely with what police members say that they need, this should be considered one component of an holistic approach that also involves evidence-based care from mental health practitioners for MI and related mental health injuries such as PTSD (Koenig et al, 2020 ), major depressive disorder (Nazarov et al, 2018 ), generalized anxiety disorder (Lee et al, 2022 ), as well as self-injurious thoughts and behaviours (Zerach & Levi-Belz, 2019 ). It has been previously reported that police chaplains can potentiate beneficial spiritual interventions for directly improving MI outcomes (Currier et al, 2023 ) as well as facilitating access to psychological services as a function of regular, direct engagements with members and outreach opportunities. Both of these were observed in the current study with the majority of chaplains describing their approach as offering flexible spiritual guidance alongside referral or encouragement to access other forms of support, thus demonstrating an appreciation of their role within the holistic model of care.…”
Section: Discussionmentioning
confidence: 99%